MANAGEMENT OF ISLAMIC RELIGIOUS EDUCATION (PAI) LEARNING BASED ON INFORMATION TECHNOLOGY (IT) - B, Abdul Aziz; Muis, Andi Abd.; Sapitri, Elsa; Nirwana, Nirwana; Masna, Masna (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The aim of this research is to determine the impact of using IT-based learning media in the learning process. The advancements in Information Technology have brought many positive impacts on the progress of education nowadays, both in hardware and software. With the developments in learning, many educational institutions are now considering the implementation of the distance learning concept as an alternative, deemed more effective and efficient. On the other hand, religious education, especially Islam, aims to shape the attitudes and personalities of Muslims who are devout to Allah SWT, with approaches involving faith, rationality, emotion, habituation, experience, and personal examples. These approaches are considered less effective for distance learning. This is because direct, effective, and continuous face-to-face interactions are needed for the above-mentioned learning approaches. Nevertheless, e-learning remains essential for Islamic religious education in the cognitive dimension.